2020
DOI: 10.1021/acs.langmuir.0c02777
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Aromatic Hydrophobic Residues on the Antimicrobial Activity and Membrane Selectivity of BRBR-NH2 Tetrapeptide

Abstract: The ultrashort linear antimicrobial tetrapeptide BRBR-NH 2 with an unnatural residue biphenylalanine (B) has potent and rapid antimethicillin-resistant Staphylococcus aureus (MRSA) activity but lacks hemolytic activity. The anti-MRSA activity of BRBR-NH 2 is 8-fold more potent than that of WRWR-NH 2 and 16-fold more potent than that of FRFR-NH 2 . However, how to influence their antimicrobial activities and mechanisms through the substitution of different aromatic hydrophobic residues is still unclear. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The research group studying UsAMPs further found that increasing the hydrophobicity of their aromatic residues, from Phe to Trp to an engineered biphenylalanine, led to deeper penetration into the hydrophobic core, stronger membrane thinning, increased membrane disruption, and more potent anti-MRSA activity. , This suggests that some of MTP’s less hydrophobic aromatic residues (like Phe in SS-20) or more strongly hydrophobic aromatic residues with hydrogen bonding capacities (like Dmt in SS-31 or Trp in SPN10) may represent an optimal design for MTPs because they do not bury as deeply into the bilayer as UsAMPs. The shallower insertion depth of MTPs may be sufficient to cause a meaningful change in the C m without causing such acute membrane thinning that the bilayer becomes vulnerable to disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research group studying UsAMPs further found that increasing the hydrophobicity of their aromatic residues, from Phe to Trp to an engineered biphenylalanine, led to deeper penetration into the hydrophobic core, stronger membrane thinning, increased membrane disruption, and more potent anti-MRSA activity. , This suggests that some of MTP’s less hydrophobic aromatic residues (like Phe in SS-20) or more strongly hydrophobic aromatic residues with hydrogen bonding capacities (like Dmt in SS-31 or Trp in SPN10) may represent an optimal design for MTPs because they do not bury as deeply into the bilayer as UsAMPs. The shallower insertion depth of MTPs may be sufficient to cause a meaningful change in the C m without causing such acute membrane thinning that the bilayer becomes vulnerable to disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Like MTPs, most AMPs are amphipathic and strongly cationic; unlike MTPs, AMPs exert their MoA by disrupting membranes and inducing bacterial cell lysis. It is worth noting that AMP (and other related small peptide)–membrane interactions have been heavily studied using MD simulations. Of particular relevance is a family of synthetic ultrashort antimicrobial tetrapeptides (UsAMPs) for methicillin-resistant Staphylococcus aureus (MRSA) infections. These peptides share the same alternating cationic–aromatic sequence motif as MTPs but have two arginines instead of an arginine and a lysine. They found that replacing arginines with lysines nullified the UsAMPs’ anti-MRSA activity, possibly because arginines mediate rapid binding to negatively charged bilayers and their planar gaunidinium group can coordinate multiple lipid phosphates, potentially leading to increased bilayer defects. ,, This suggests that the Arg–Lys pair in MTPs may be optimal because it can weakly coordinate anionic lipids such as TOCL and alter membrane electrostatics without disrupting membranes such as the UsAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Alapropoginine was also conjugated to a carbon side chain composed of 2-(6-methoxynaphthalen-2-yl)propanoic acid. The rationale behind the conjugation strategy is to sustain the hydrophobic grip of the biphenylalanine amino acids and provide a hydrophobic stabilizer to the peptide [33].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations in conjunction with enhanced sampling method provide an effective tool for revealing protein–membrane interactions at the atomistic level and complementing experimental results [ 6 , 7 , 8 , 9 ]. The first category of studies [ 4 , 10 , 11 , 12 , 13 , 14 , 15 ] typically involves placing monomeric or oligomeric toxin proteins/antibacterial peptides either on the surface of bilayer membrane or directly in a transmembrane helical state, with a focus on investigating local structural characteristics such as changes in membrane properties and peptide conformations via conventional molecular dynamics (CMD) simulations. Steinbrecher et al [ 10 ] studied the protein–lipid interaction and structures of monomeric, dimeric, and oligomeric TisB toxin proteins by using coarse-grained MD simulation.…”
Section: Introductionmentioning
confidence: 99%